ANALISA FUNGSI JAMINAN DALAM PEMBIAYAAN MUDHARABAH - Jamilah, Wardah (Al-Infaq: Jurnal Ekonomi Islam, 2012)
This paper attempts to analyze collateral function in mudharabah financing. Basically collateral serves is the security for the instruments of financial institutions, as well as the practice of mudharabah financing. And in any investment is always risky, both small and big risk. To minimize risks, the Islamic banks apply in any financial assurance functions, as well as the mudharabah financing. Based on the analysis of the function of financing collateral, if collateral is sold, the selling price should be higher than the loan amount, the reason is always the guarantee liquidity value. Function guarantees required in the financing agreement, carried out using the analysis of bank financing to obtain reasonable assurance that the financing provided by the customer will be refunded. Aspects guarantee is intended to determine liability in the form of customers' intention to pay. Analysis of security is also intended to know the eligibility guarantee of the legal aspects and the material associated with the financing provided to the prospective customer financing. The most important role is to guarantee the handling of non-performing financing, by way of executing the guarantee. That guarantees a right of ownership or moved by selling insurance, to pay off the arrears that have not been completed, and in order for financing customers always have a sense of responsibility for the funds that have been borrowed, due to the condition that the funds are not wholly-owned bank disbursed funds but third party may at any time withdraw such funds. The application functions as an instrument intended collateral securing repayment of financing sources is when the customer has no ability to pay installments intentions, and if the customer breaks the promise with indications of fraud or intentional element. But such execution of guarantees should be in the way of agreement between customer and the bank.